The relation between public municipal investment and quality of life in the metropolitan cities of Chile - Orellana, Arturo; Marshall, Catalina (Pontifícia Universidade Católica de São Paulo, 2017)
Urban quality of life is one of the main concerns of metropolitan cities in Latin America. According to many studies, it is possible to notice that there is a significant pattern of territorial inequality which usually affects the largest part of the local population. In the case of Chile, the reality faced by the metropolitan cities around Santiago, Valparaíso and Concepción, follows this trend, and the role played by municipal investment is particularly relevant. From this perspective, this study investigates the impact of municipal investment on urban quality of life. Public municipal investment undergoes a more detailed analysis. We found that the financing mechanisms that operate with greater autonomy from the federal government – basically, municipal and regional investment – do not have a significant impact on urban quality of life, and private investment becomes more present, although in a discretionary fashion.